Nano- Wire Structure Optimization to Achieve High Sensibility and Frequency Response - Ghahri, MR; Hasani, SS (International Journal of Computer Sciences and Engineering, 2025)
In this paper the structure of Nano- Wire would be optimized to achieve high sensibility and frequency response. To perform this optimization, the length of Nano- Wire g region and the thickness of absorber layer will be optimized. Silvaco software is used for simulation and optimization. The proposed structure includes a window profile is used for Nano- Wire.